Ubiquitous and Pervasive Computing New Trends and Opportunities - da Rosa Righi, Rodrigo (IntechOpen, 2023)
We are living in an age of digital transformation, where internet connectivity is totally transparent for end users. Since the development of internet of things technologies and artificial intelligence algorithms, we have also been experiencing new business models and applications. In Ubiquitous and Pervasive Computing - New Trends and Opportunities, novel concepts and applications in this area are described, and the expectations and challenges of the next ten years are discussed. Individual chapters focus on data science, the internet of things, big data, Industry 4.0, high-performance computing, intelligent applications, and cloud computing environments.